Aggregate history of user mobility pattern for QoS provisioning in multimedia wireless networks - ,, Prihandoko; Habaebi, Mohamed Hadi; Ali, Borhanuddin M. (Springer, 2004)
Multimedia traffic is expected to be included in the next generation of wireless networks. As in wireline networks, the wireless network must also be capable of providing guaranteed quality of service (QoS) over the lifetime of mobile connections. Some challenging problems appear in multimedia wireless networks, such as user mobility and shortage of bandwidth, influence the QoS provisioning for the users. In this paper, a bandwidth reservation scheme incorporating a user mobility prediction is proposed to manage the QoS of the networks. The mobility prediction scheme is developed based on the aggregate history of mobile users. Based on the mobility prediction, bandwidth is reserved to guarantee the uninterrupted handoff process. Simulation results demonstrate that the proposed scheme can guarantee the required QoS requirements in terms of handoff call dropping probability and new call blocking probability while maintaining efficient bandwidth utilization.